Introduction word: Men’s Health Journal (MHJ) - Hosseini, Jalil (Archives of Men's Health, 2018)
Men's health is globally a relatively new debate that has attracted academic communities from the 1990s in identifying, preventing and treating specific conditions and men's common diseases. Considering the importance of men's health in accordance to policy makers’ and scientific communities’ opinion in different countries as a result of research development, publications and scientific productions in this field, it is necessary to publish the outcome of these researches and articles. Thus, according to personal interest in the men's health and its foundation in Iran, as well as the main mission of our Research Center2 and the necessity of focusing different specialists on this issue, we decided to offer the Men's Health Journal. We hope by the participation of interested scientists and researchers in the field of Men’s health around the world, we will observe the wide contribution of different specialists who are interested in promoting men’s health in the world.